Family Socioeconomic Status, Cortisol, and Physical Health in Early Childhood: The Role of Advantageous Neighborhood Characteristics - Roubinov, Danielle S. (Psychosom Med, 2018)
OBJECTIVE: Children from families with lower socioeconomic status (SES) evidence greater physiological dysregulation and poorer health. Despite recognition of environmental contributors, little is known about the influence of neighborhood characteristics. The present study examined the moderating role of community-level risks and resources on the relation of family SES to children’s daily cortisol output and physical health during the kindergarten year. METHODS: In fall and spring of kindergarten, children’s (n = 338) daily total cortisol was measured and parents and teachers rated children’s global physical health. Parents reported family SES. Neighborhood characteristics were assessed using the Child Opportunity Index (COI), a population-level tool that evaluates the quality of multiple domains of neighborhood attributes. RESULTS: In fall, children reared in lower SES family environments had higher cortisol when residing in lower quality (lower opportunity) neighborhoods (b = −.097, p < .001), but there was no relation between family SES and children’s cortisol in more advantaged (higher opportunity) neighborhoods (b = −.023, p = .36). Lower family SES was prospectively associated with poorer physical health in spring (controlling for fall health) only among children living in lower opportunity neighborhoods (b = −.250, p = .018) and was unrelated to physical health among children residing in higher opportunity neighborhoods (b = .042, p = .70). CONCLUSION: Higher opportunity neighborhoods may protect against the negative consequences of low family SES on children’s stress physiology and physical health. Public health interventions that bolster neighborhood opportunities may benefit young children reared in socioeconomically disadvantaged family environments.